IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) STUDI KASUS DI SD NEGERI BALEKAMBANG 01 PAGI KECAMATAN KRAMAT JATI - Firdaus, Arief Nurul (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the implementation of the zoning system policy in New Student. Admissions (PPDB) at State Elementary School of Balekambang 01 Pagi, Kramat Jati District, based on George Edward III’s theory. This policy is based on the Ministry of Education, Culture, Research, and Technology Regulation No. 1 of 2021, the Special Region of Jakarta Governor Regulation No. 15 of 2024, and Decree of the Head of the Special Region of Jakarta Provincial Education Office No. 92 of 2024. This study examines the success of policy implementation through the four key elements of Edward III’s theory: communication, resources, disposition, and bureaucratic structure. The findings indicate that the policy implementation has supported the equitable access to education; however, several challenges were identified, including suboptimal policy socialization, limited school facility capacity, and resistance from the community. The solutions implemented by the school include enhancing socialization efforts, utilizing a digital system for registration, and proposing infrastructure capacity improvements. This study also provides recommendations to improve the effectiveness of the zoning policy, such as improving cross-sector communication, increasing school capacity, and ensuring equitable quality education. These findings have important implications for the future development of the zoning policy to create more inclusive and  equitable access to education.